The Problem of Professional burnout of Post-primary School Teachers on the Basis of a Study of Teachers from West Pomerania Province - Chmielewska, Ewa (Journal of Education, Technology and Computer Science, 2021)
Professional burnout syndrome is undoubtedly another civilisation disease that affects modern societies. In May 2021 professional burnout was included within the list of the WHO International Classification of Diseases, however, not as a disease, but as an occupational syndrome significantly affecting health of an employee. However, it is worth noting that it is only from 2022 that professional burnout will have become a disease which will need to be treated. The research presented below shows that there are many factors which cause this new disease, and stress is among the main ones. Working as a teacher, which is considered one of the professions of supportive nature, means being exposed to various stress factors. One of the most dangerous effects is professional burnout which can lead, among others, to many health disorders, subjective treatment of students, and ultimately, make teachers resign from their job.